3-DIMENSIONAL HYDRODYNAMICS MODELING BEFORE AND AFTER CONSTRUCTION OF PATIMBAN PORT, SUBANG REGENCY - Yudicia Isnaeni, Kholillah
This study aims to describe hydrodynamic conditions both horizontally and vertically in Subang waters before and after the construction of Patimban Port (2018 – 2021). Patimban Port is one of the vital objects built in the coastal area, specifically on the coast of Eretan Bay, the Java Sea. In Eretan Bay, the mouth of the Cipunagara River has a daily discharge of hundreds of cubic meters during the westerly wind season (DJF). The high intrusion of discharge into semi-enclosed bay waters and the construction of a port that can change hydrodynamic conditions result in the need to study hydrodynamic conditions in Patimban waters. The simulation used a numerical model developed by Deltares (DELFT3D) to produce 3D outputs of salinity, temperature, and currents with five layers of depth and 2D outputs of water level. The simulation was carried out with two domains (from Jakarta – Pemalang and Patimban waters) and four scenarios using a structured grid. The grid resolution in Domain 1 is 1 km, and Domain 2 is 22 – 44 m. Bathymetry and shoreline data were used to build the mesh. Domain 1 uses BATNAS for the bathymetry and RBI for coastline data. Domain 2 uses the assimilation of BATNAS and DEMNAS for bathymetry and river depth data. For coastline data, domain 2 uses the assimilation of RBI and LANDSAT 8 data. For boundary conditions, tidal data (astronomical), temperature, and salinity were used. Meanwhile, the pressure and wind data are the forces acting in all domains but only on the surface. Verification of model results in the form of water level against three tidal observation stations showed good results, namely 0.07 - 0.09 for RMSE and 0.9 for CC. Verification of the temperature showed an RMSE value of 0.29 MSE value of 0.08, and MAE value of 0.27. For currents, the RMSE value was good for tidal currents with a value of 0.09, while for total currents, the MSE and MAE were calculated, which amounted to 0.021 and 0.09. The verification results show that the error range of the model is still acceptable. The model results show that hydrodynamic conditions in Patimban waters are influenced by wind during high wind speed conditions (>3.5 m/s) and river discharge during high discharge conditions. Tides affect circulation when wind and discharge are weak. The input of river discharge allows vertical variations in temperature and salinity values in shallow waters that should be a mixed layer (uniform). The simulation results show that in the presence of port buildings there is a deflection of current direction on the west and south sides of the port and a decrease in current magnitude on the south side of the port both at high and low tide. There is an increase in current magnitude on the east side of the harbor at low tide. The increase and decrease in current magnitude ranges from 0.05 - 1 m/s. The presence of port buildings also causes a blocking effect so that low temperature and salinity values from river discharge seem to be trapped on the south side of the port and cannot be distributed to the east side of the port. The decrease in temperature value that occurs reaches 0.5 ºC while in salinity the decrease in salinity value reaches 3 ppt. Vertically the decrease and variation of salinity values in the area around the harbor is more significant when compared to temperature. The discharge intrusion is wider at low tide which is characterized by a wider distribution of low temperature and salinity. The trapped temperature and low salinity values can occur because both parameters experience slow changes when compared to changes in the current. The circulation that occurs in Patimban waters is very dependent on the magnitude of the forces acting in these waters, because the currents that occur will follow the pattern of the dominant force (the magnitude of the large force). The existence of significant changes in hydrodynamic conditions due to port development means that port development needs to pay attention to the hydrodynamic conditions of the port so that the development does not damage the natural conditions of the waters.